Dicrostonyx torquatus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
39. Palearctic Collared Lemming Dicrostonyx torquatus French: Lemming a collier / German: Echter Halsbandlemming / Spanish: Lemming paleértico de collar Other common names: Arctic Lemming, Collared Lemming Taxonomy. Mus torquatus Pallas, 1779, mouth of River Ob, NW Siberia, Russia. Dicrostonyx torquatus 1s in the subgenus Misothermus. In the past, it was treated as a Holarctic species, with five subspecies in Eurasia and 6-12 in North America. Evolutionary split between Palearctic and Nearctic species was first retrieved from chromosomal evidence and cross-breeding experiments and subsequently confirmed by molecular markers and morphometric data. Three subspecies recognized. Subspecies and Distribution. D.t.torquatusPallas,1779—NEEuropeanRussiaandW&CSiberia(WofYeniseiRiver). D.t.chionopaesG.M..Allen,1914—ESiberia(EofYeniseiRiver),includingBolshevikIandNewSiberianIs,EtoChukchiandKamchatkapeninsulas. D. t. ungulatus Baer, 1841 — Novaya Zemlya I (N Russia). Descriptive notes. Head—body 88-140 mm, tail 11-21 ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 298-299, DOI: 10.5281/zenodo.6707142 ...